Static Balance Norms in Children. (23rd May 2013) - Condon, Cillin; Cremin, Katie
Abstract Objectives The ability to sustain single leg stance and tandem stance is often used to determine the balance abilities of children, particularly after ankle or foot injury. The aim of this study was to assess performance norms on timed static balance tests in children aged 4 to 15 years. Design Cross‐sectional study Methods Children from schools across the Republic of Ireland (n = 534) were tested on six balance tests as well as a standing broad jump. Results Interquartile ranges for the tests are presented for each age group (4–5, 6–7, 8–9, 10–11 and 12+ years). The results confirm the improvement in balance performance as children age especially after the 7 to 8th year. Girls tend to outperform boys across all balance tests. There is a ceiling effect for some single leg stance and tandem stance tests after the age of 7 years. Conclusions Results can be used for comparative purposes against age appropriate normative balance test scores. This removes the estimation from balance testing and the risk of applying an insufficient cut‐off time. Copyright © 2013 John Wiley & Sons, Ltd.